Tourism Opportunities of Boysun District and Their Use - Ziyodullayeva Ogilshod Eshniyoz qizi (Universitas Muhammadiyah Sidoarjo, 2022)
The article presents the tourism opportunities and opportunities of Boysun district. It describes the facilities that serve tourism in the Baysun district and their future opportunities, which are unique.